2023
DOI: 10.1017/dmp.2023.7
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Isolation and Mental Health Among Children

Abstract: Objective: Mental health issues increased during the COVID-19 pandemic, especially among children. Our past research efforts found that surveillance data can address a variety of health concerns; that personal psychological awareness impacted ability to cope, and mental health outcomes were improved when survivors were triaged to mental health countermeasures. To build upon our public health efforts we wanted to see if increased screen time due to remote learning caused by the pandemic influenced school a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…No texto construído por (Brannen DE et al, 2023) edifica-se uma ligação entre a quantidade de dias que a criança fica em isolamento social com diagnóstico de transtornos de humor, corroborando as ideias citadas nos parágrafos anteriores.…”
Section: Discussionunclassified
“…No texto construído por (Brannen DE et al, 2023) edifica-se uma ligação entre a quantidade de dias que a criança fica em isolamento social com diagnóstico de transtornos de humor, corroborando as ideias citadas nos parágrafos anteriores.…”
Section: Discussionunclassified
“…Future research is needed to better understand equity issues regarding the impact of the pandemic on cyberabuse victimization among sexual and gender minority individuals, as some literature has shown that both sexual and gender minority groups experience disparate rates of technology-faciliated abuse (Powell et al, 2020). Finally, the potential for negative impact on older (and younger) age groups under periods of social isolation is obvious and has been examined since the early days of the COVID19 pandemic (e.g., Almeida et al, 2021; Brannen et al, 2023; Chang & Levy, 2021); future research may follow the current design with different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation (SI) induces lasting negative effects on the brain, and these effects could be more powerful or distinctly different when SI occurs during vulnerable periods, such as adolescence. Social isolation could result in lasting behavioral abnormalities and neuropsychiatric disorders, including aggression, substance addiction, obsessive-compulsive disorder, and eating disorders [129][130][131]. Adolescents, especially girls, are more likely to suffer from anxiety and depression during and after SI [132].…”
Section: Isolation/individual Housingmentioning
confidence: 99%